2019
DOI: 10.1186/s12958-019-0511-x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive functions of Kisspeptin/KISS1R Systems in the Periphery

Abstract: Kisspeptin and its G protein-coupled receptor KISS1R play key roles in mammalian reproduction due to their involvement in the onset of puberty and control of the hypothalamic-pituitary-gonadal axis. However, recent studies have indicated a potential role of extra-hypothalamic kisspeptin in reproductive function. Here, we summarize recent advances in our understanding of the physiological significance of kisspeptin/KISS1R in the peripheral reproductive system (including the ovary, testis, uterus, and placenta) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 80 publications
0
72
0
Order By: Relevance
“…In addition, exogenous administration of Lif, but not E2, partially rescues implantation failure in Kiss1 knockout mice and data show that E2 significantly increases uterine kiss1 mRNA expression in ovariectomized mice . These data suggest that KP signaling may act downstream of E2 to stimulate uterine Lif expression and is beneficial for promoting embryo implantation and decidualization in mice …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, exogenous administration of Lif, but not E2, partially rescues implantation failure in Kiss1 knockout mice and data show that E2 significantly increases uterine kiss1 mRNA expression in ovariectomized mice . These data suggest that KP signaling may act downstream of E2 to stimulate uterine Lif expression and is beneficial for promoting embryo implantation and decidualization in mice …”
Section: Discussionmentioning
confidence: 83%
“…54 These data suggest that KP signaling may act downstream of E2 to stimulate uterine Lif expression and is beneficial for promoting embryo implantation and decidualization in mice. 55 It is well known that maternal serum hCG peaks at 8-10 weeks of gestation and then declines to reach a plateau at 18-20 weeks of gestation, 56 while the level of KP continues to rise throughout gestation into the 3rd trimester and, unlike hCG, does not plateau. 57 No substantial correlation between KP and hCG rates in viable intrauterine pregnancy, whereas in spontaneous abortions there is a significant correlation between KP and hCG levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is variability in the cell types observed to express kisspeptin or its receptor (see Table 1 and Figure 1). Some of these differences observed may be due to variation between species, age differences within the species and the different experimental methods employed [45]. [12,[19][20][21]42], round [12], and elongated spermatids [20].…”
Section: Distribution Of Kisspeptin and Its Receptormentioning
confidence: 99%
“…In female reproductive tissues, kisspeptins are involved in the regulation of a wide variety of processes including follicular development, oocyte maturation, ovulation, ovarian steroidogenesis, embryo implantation, and placentation [53][54][55][56]. In the case of males, kisspeptins are suggested to play important regulatory roles in spermatogenesis, testicular steroidogenesis, and spermatozoa function, as is discussed in the following sections [43,54].…”
Section: Kisspeptinsmentioning
confidence: 99%
“…In another study involving the amphibian Pelophylax esculentus, researchers cultured their testes-obtained in their reproductive period-and observed that kisspeptin accelerated germ cell progression [79]. As for mammals, gene expression studies performed in mice revealed that KISS1/KISS1R expression initiation in testis coincides with the formation of spermatozoa [54,72]. In addition, a cross-sectional study performed in human showed that kisspeptin was present in seminal plasma.…”
Section: Spermatogenesismentioning
confidence: 99%